Comparative MicroRNA Expression Profiles of Cynomolgus Monkeys, Rat, and Human Reveal that miR-182 Is Involved in T2D Pathogenic Processes. (3rd November 2014) - Zhou, Jinghui; Meng, Yuhuan; Tian, Shuai; Chen, Junhui; Liu, Mingyu; Zhuo, Min; Zhang, Yu; Du, Hongli; Wang, Xiaoning
Abstract : Type 2 diabetes (T2D) is a prevalent disease that happens around the world and usually happens with insulin resistance. MicroRNAs (miRNAs) represented important roles in the suppression of gene expression and were proven to be related to human diseases. In this study, we used cynomolgus monkey fed with normal and high fatty diet (HFD), respectively, to analyze the miRNA expression profile in whole blood by deep sequencing. Finally in total 24 miRNAs with differential expression were filtered. Among them, miR-182 related to the insulin resistance by modulating FOXO1 and PI3K/AKT cascade and had the greatest copy number in the whole blood. Decrease of miR-182 in T2D cynomolgus individuals is completely consistent with the previous studies in human and rat. Integrating miR-182 tissue expression profile, target genes, and copy number in blood reveals that miR-182 plays a key role in crucial genes modulation, such as FOXO1 and BHLHE22, which leads to potential hyperglycemia and modulates the insulin secretion. In addition, miR-182 might regulate the processes of both cell proliferation and apoptosis that play crucial role in determining the cells' fate. Therefore, miR-182 can be a biomarker in diagnosis of the potential T2D that has benefits for medical purpose.